Cretaceous and Eocene tectono-thermal events determined in the Inner Western Carpathians orogenic front Infratatricum - Putiš, M.; Danišík, Martin; Siman, P.; Nemec, O.; Tomek, Č.; Ružicka, P. (POLISH GEOLOGICAL INST, 2019)
This paper re-assesses the tectono-thermal evolution of the frontal Infratatricum part of the Inner Western Carpathians orogen based on new geological-petrological and zircon fission track (ZFT) data and published 40Ar-39Ar and K-Ar data. The study area is in the Považský Inovec Mts. in Western Slovakia, where the Infratatric Inovec Nappe comprises a micaschist-gneiss basement and Upper Carboniferous-Lower Cretaceous cover with the Jurassic-Lower Cretaceous Humienec Succession; this latter is reconstructed from olistoliths in the Horné Belice Succession Upper Cretaceous flysch. The Infratatric Inovec Nappe posterior part is thrust over its frontal Humienec tectonic Slice with infolded Upper Cretaceous sediments. This nappe exhibits very low-temperature tectono-thermal overprinting, and this is documented by electron probe microanalysis of metamorphic phases and P-T estimates. The late Early Cretaceous age of this D1 stage event at approximately 115-95 Ma is recorded by 114 ±2 and 106 ±4 Ma phengitic white mica 40Ar-39Ar ages from a Lower Cretaceous cherty slate, and by 101 ±3 Ma 40Ar-39Ar age and 102±4 Ma ZFT age from Permian meta-sandstone. The Inovec Nappe was thus derived from an Albian-Early Cenomanian accretionary wedge. The hemipelagic Upper Turonian to Lower Santonian red marls and upward syn-orogenic Upper Santonian to Maastrichtian flysch were deposited on the frontal attenuated part of the Inovec Nappe-type basement in the inferred Pieninic-Váhic (~South-Penninic) zone. This flysch contains olistolithic to clastogeneous metamorphosed material, including the Lower Cretaceous slates, supplied from the posterior part of the Inovec Nappe. The 40Ar-39Ar age of 86 ±2 Ma from this nappes’ Permian meta-sandstone is consistent with D2 thrusting at approximately 95-85 Ma and Horné Belice foreland flysch basin supply in the D3 stage at ~85-65 Ma. The Inovec Nappe frontal Humienec tectonic Slice with infolded Upper Cretaceous sediments suggests formation of a Paleocene-Eocene accretionary wedge at approximately 65-40 Ma in the D4 stage. This event is constrained by 40Ar-39Ar age of 48 ±2 Ma from the Tatricum hanging wall blastomylonites and whole-rock K-Ar age of 46 ±3 Ma from a Permian basalt olistolith in the footwall Infratatricum Horné Belice flysch. The Infratatricum finally became part of an Eocene accretionary wedge north of the Hrádok-Zlatníky thrust-fault, and reheating and exhumation cooling is documented by 57-37 Ma ZFT ages. Although the Infratatricum exhibits Late Cretaceous and Eocene tectono-thermal imprints, it is a remnant of the Early Cretaceous structure at the Inner Western Carpathian front. This imposes the Infratatricum as a distal continental margin of the Penninicum.